Beyond motor neurons: expanding the clinical spectrum in Kennedy's disease. Issue 8 (20th January 2018) - Manzano, Raquel; Sorarú, Gianni; Grunseich, Christopher; Fratta, Pietro; Zuccaro, Emanuela; Pennuto, Maria; Rinaldi, Carlo
Abstract : Kennedy's disease, or spinal and bulbar muscular atrophy (SBMA), is an X-linked neuromuscular condition clinically characterised by weakness, atrophy and fasciculations of the limb and bulbar muscles, as a result of lower motor neuron degeneration. The disease is caused by an abnormally expanded triplet repeat expansions in the ubiquitously expressed androgen receptor gene, through mechanisms which are not entirely elucidated. Over the years studies from both humans and animal models have highlighted the involvement of cell populations other than motor neurons in SBMA, widening the disease phenotype. The most compelling aspect of these findings is their potential for therapeutic impact: muscle, for example, which is primarily affected in the disease, has been recently shown to represent a valid alternative target for therapy to motor neurons. In this review, we discuss the emerging study of the extra-motor neuron involvement in SBMA, which, besides increasingly pointing towards a multidisciplinary approach for affected patients, deepens our understanding of the pathogenic mechanisms and holds potential for providing new therapeutic targets for this disease.